The Effect of Dividend Policy, Earnings Volatility, and Leverage on Stock Price Volatility - Khasanah, Umi; Wijaya, Lihan Rini Puspo; Sidik, M. Muhayin A. (Penerbit Goodwood, 2025)
Purpose: This study aims to measure the effect of dividend policy, earnings volatility, and leverage on the stock price volatility of retail companies during the period 2020-2024. Methodology/approach: The study utilizes secondary data obtained from the financial statements of retail companies listed on the Indonesia Stock Exchange (IDX) from 2020-2024. The sample was selected using purposive sampling, and multiple regression analysis was conducted using SPSS 26 software test the hypotheses Results/findings: The study shows that dividend payout ratio, dividend yield, earnings volatility, and leverage simultaneously influence stock price volatility. The adjusted R2 value of 0,127 indicated that the four independent variables explain 12,75 of the variation in stock price volatility. Conclusions: Stock price volatility of retail companies is influenced by earnings volatility and leverage. However, the dividend payout ratio and dividend yield do not have a significant effect on stock price volatility. Limitations: This study only covers dividend policy, earnings volatility, and leverage variables, without considering external factors such as macroeconomic condition or industry characteristics. Contribution: These findings are useful for companies in evaluating financial performance, for investors in assessing investment risk, and for academics as a reference regarding the relationship between financial structure and stock price volatility.